Janus particles for (bio)sensing. (December 2017) - Yánez-Sedeño, P.; Campuzano, S.; Pingarrón, J.M.
Graphical abstract: Highlights: Janus nanoparticles in optical and electrochemical (bio)sensing. Interesting possibilities for relevant analytes (bio)sensing in static and dynamic modes. Suitability for designing single- or multiplexed (bio)sensing strategies for target analytes of different nature. Abstract: This review article sheds useful insight in the use of Janus nanoparticles for (bio)sensing in connection with optical and electrochemical transduction. After a brief introduction of the main properties, types and fabrication strategies of Janus nanoparticles, selected applications for their use in electrochemical and optical biosensing are critically discussed. Highlighted examples illustrate the great versatility and interesting possibilities offered by these smart multifunctional nanoparticles for (bio)sensing of relevant analytes operating both in static and dynamic modes. Progress made so far demonstrate their suitability for designing single- or multiplexed (bio)sensing strategies for target analytes of different nature (organic and inorganic compounds, proteins, cells and oligomers) with relevance in clinical (H2 O2, glucose, cholesterol, CEA, human IgG, propranolol, bacterial and tumor cells) and environmental (lead and organophosphorous nerve agents) fields. Key future challenges and envisioned opportunities of the use of Janus nanoparticles in the (bio)sensing field are also discussed.